What Can We Learn from Nutrition Impact Evaluations? Lessons from a Review of Interventions to Reduce Child Malnutrition in Developing Countries - Independent Evaluation Group (Washington, DC: World Bank, 2012)
This paper reviews recent impact evaluations of interventions and programs to improve child anthropometric outcomes- height, weight, and birth weight-with an emphasis on both the findings and the limitations of the literature and on understanding what might happen in a non-research setting. It further reviews the experience and lessons from evaluations of the impact of the World Bank-supported programs on nutrition outcomes. Specifically, the review addresses the following four questions: 1) what can be said about the impact of different interventions on children's anthropometric outcomes? 2) How do these findings vary across settings and within target groups, and what accounts for this variability? 3) What is the evidence of the cost-effectiveness of these interventions? 4) What have been the lessons from implementing impact evaluations of Bank-supported programs with anthropometric impacts? Although many different dimensions of child nutrition could be explored, this report focuses on child anthropometric outcomes-weight, height, and birth weight. These are the most common nutrition outcome indicators in the literature and the ones most frequently monitored by national nutrition programs supported by the World Bank. Low weight for age (underweight) is also the indicator for one of the Millennium Development Goals.